An analysis of business problems and its sources (ХІХ c. – the ХХ c.) (Journal of history, 2019)
The paper studies the process of formation of new business concepts in the field of entrepreneurship in Kazakhstan.To prove the seriousness of this problem, the author has paid special attention to the history of the business of the southern region. In the process of studying the history of the business, industry, trade, agricultural and service sectors author tried to make a comparative analysis of the problem.The first article about the studied subject was written in 1860. In the course of studying the history of pre-revolutionary period of entrepreneurship is necessary to allocate the works of SK Igibaeva.As a result of this writing, the author has collected a large number of sources which in the course of a thorough analysis is divided into four main groups.